Rozważania o rewolucji. Antykomunistyczne piśmiennictwo w II Rzeczypospolitej o bolszewickich dążeniach zorganizowania buntu mas. Zarys problemu - Sacewicz, Karol (Przegląd Wschodnioeuropejski, 2025)
The Bolshevik revolution changed not only Russia, but the history of the countries of Eastern and Central Europe. Expansive communism, when it could not be exported directly to the West as a result of the defeat of the Red Army on the outskirts of Warsaw in 1920, was to be spread by the revolutionary revolts of the masses, in accordance with the will of the Kremlin, transmitted through the Comintern. These were to be inspired by the Bolsheviks, and then by the Soviet state. This threat became the subject of scientific and journalistic discourse in interwar Poland, a discourse about the essence of the Bolshevik revolution, its goals and executors, about what it meant to its ideologues and how it was perceived by Polish analysts, researchers and social activists.